2014
DOI: 10.1186/1824-7288-40-54
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypovitaminosis D and predictors of vitamin D status in Italian healthy adolescents

Abstract: BackgroundVitamin D plays an important role in health promotion during adolescence. Vitamin D deficiency and insufficiency are common in adolescents worldwide. Few data on vitamin D status and risk factors for hypovitaminosis D in Italian adolescents are currently available.Methods25-hydroxyvitamin D (25-OH-D) and parathyroid hormone (PTH) levels were evaluated in 427 Italian healthy adolescents (10.0-21.0 years). We used the following cut-off of 25-OH-D to define vitamin D status: deficiency < 50 nmol/L; insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
76
3
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 38 publications
23
76
3
11
Order By: Relevance
“…In contrast to data from past studies indicated that season of blood withdrawal was a significant predictor of vitamin D status, with identification of lower median 25(OH) D levels during winter and spring [36] [37] [38], seasonal alteration had no influence on 25(OH) D levels as well as corrected calcium levels in our study population, whereas serum PTH levels were higher in summer cases, especially among females. Lack of the effect of seasonal difference on serum vitamin D levels was also reported in a past study in stroke patients which revealed similar levels for vitamin D levels between the cases in summer (Apr-Sep) and winter (Oct-Mar) [39].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In contrast to data from past studies indicated that season of blood withdrawal was a significant predictor of vitamin D status, with identification of lower median 25(OH) D levels during winter and spring [36] [37] [38], seasonal alteration had no influence on 25(OH) D levels as well as corrected calcium levels in our study population, whereas serum PTH levels were higher in summer cases, especially among females. Lack of the effect of seasonal difference on serum vitamin D levels was also reported in a past study in stroke patients which revealed similar levels for vitamin D levels between the cases in summer (Apr-Sep) and winter (Oct-Mar) [39].…”
Section: Discussioncontrasting
confidence: 54%
“…In this regard, our findings may emphasize the insufficient exposure to sunlight even in summer months during which sun exposure is more effective in promoting vitamin D activation as well as its storage for an optimal vitamin D status during the remaining months of the year [36].…”
Section: Discussionmentioning
confidence: 87%
“…In particular, a recent study conducted on over 400 healthy adolescents in Tuscany (10-21 years old) showed a prevalence of hypovitaminosis D equal to 82.2%, with 32.3% of insufficiency and 49.9% of deficiency [17]. These results suggest that the high percentage of hypovitaminosis D observed in our series might be primitive and probably gained before the onset of the disease.…”
Section: International Journal Of Digestive Diseasessupporting
confidence: 57%
“…Among those with deficiency, Nonwhite adolescents had a higher prevalence of severe vitamin D deficiency than white adolescents. Adolescents who performed <3 hours/week of outdoor exercise had higher prevalence of hypovitaminosis D [10].…”
Section: Introductionmentioning
confidence: 99%